2009
DOI: 10.1097/prs.0b013e318199f46e
|View full text |Cite
|
Sign up to set email alerts
|

Nasoalveolar Molding Improves Long-Term Nasal Symmetry in Complete Unilateral Cleft Lip–Cleft Palate Patients

Abstract: The data demonstrate that the lower lateral and septal cartilages are more symmetric in the nasoalveolar molding patients compared with the surgery-alone patients. Furthermore, the improved symmetry observed in nasoalveolar molding-treated noses during the time of the primary surgery is maintained at 9 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(130 citation statements)
references
References 19 publications
4
121
0
5
Order By: Relevance
“…This study evaluated the effects of NAM on the nasoalveolar morphology until 18 months of age. So far, the longest follow up study for NAM has been carried out by BARILLAS et al 2 They evaluated the long term (9 years) nasal symmetry in complete UCLP patients following NAM and concluded that the lower lateral and septal cartilages are more symmetric in the nasoalveolar moulding patients compared with the surgery-alone patients. The improved symmetry observed in nasoalveolar moulding-treated noses during the time of the primary surgery is maintained at 9 years of age.…”
Section: Discussionmentioning
confidence: 97%
“…This study evaluated the effects of NAM on the nasoalveolar morphology until 18 months of age. So far, the longest follow up study for NAM has been carried out by BARILLAS et al 2 They evaluated the long term (9 years) nasal symmetry in complete UCLP patients following NAM and concluded that the lower lateral and septal cartilages are more symmetric in the nasoalveolar moulding patients compared with the surgery-alone patients. The improved symmetry observed in nasoalveolar moulding-treated noses during the time of the primary surgery is maintained at 9 years of age.…”
Section: Discussionmentioning
confidence: 97%
“…The survey strategy resulted in 319 articles, of which 12 were qualified for the final analysis in the first survey (eight RCTs, four CCTs) (Karling et al, 1993;Ross and MacNamera, 1994;Chan et al, 2003;Konst et al, 2003b;Bongaarts et al, 2004;Prahl et al, 2005Prahl et al, , 2008Bongaarts et al, 2006;Masarei et al, 2007;Bongaarts et al, 2008;Barillas et al, 2009;Bongaarts et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of appliance design, one controlled study was retrieved on the nasolaveolar molding (NAM) approach (Barillas et al, 2009). Active palates were evaluated in two articles (Chan et al, 2003;Masarei et al, 2007) and passive plates in eight (Ross and MacNamera, 1994;Konst et al, 2003b;Bongaarts et al, 2004;Prahl et al, 2005Prahl et al, , 2008Bongaarts et al, 2006;Bongaarts et al, 2008;Bongaarts et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that when instituted at 1 week of age and continued for 3 to 4 months, NAM is effective in approximating the cleft as well as improving the nasal deformity. Specifically, patients undergoing NAM treatment experienced improved nasal alar symmetry, columella lengthening, and nasal tip projection [29][30][31][32] (Levels II to V evidence). The counter arguments include nasal relapse and maxillary growth constriction.…”
Section: Other Therapeutic Optionsmentioning
confidence: 97%